Impact of real shocks on business cycles in selected Sub-Saharan African countries - Barnabas Amu; Evans Osabuohien; Philip Alege; Jeremiah O. Ejemeyovwi (Cogent Business & Management, 2021)
This study examines business cycle fluctuations in selected Sub-Saharan African (SSA) countries. The study measures the impact of selected real shocks, namely: terms of trade shocks, commodity price shocks, and government spending shocks, on macroeconomic fluctuations in SSA. The impact of the selected shocks was measured by the Bayesian Panel Vector Autoregression (BPVAR) technique. It was ascertained from the results that real (i.e. productivity) shocks drive business cycles (macroeconomic fluctuations) in SSA countries which support theoretical inclination. Furthermore, from the empirical analysis, terms of trade shocks possess the highest positive impact on business cycles. At the same time, government expenditure has the highest negative impact on business cycle among the three selected real shocks across the SSA region. Thus, the study recommends that government institutions in SSA should embark on sound fiscal policy plan along with monetary policy to stabilise the economy during recessions and expansions. The study highlights the need for diversification of the export base of SSA countries to mitigate terms of trade losses usually occasioned by unfavourable commodity price shocks.
Keywords: C11; C33; E19; F44; 650; Bayesian panel VAR; macroeconomic fluctuations; real business cycle; real shocks; Sub-Saharan Africa